2013
DOI: 10.1126/scisignal.2003573
|View full text |Cite
|
Sign up to set email alerts
|

Kinase-Substrate Enrichment Analysis Provides Insights into the Heterogeneity of Signaling Pathway Activation in Leukemia Cells

Abstract: Kinases determine the phenotypes of many cancer cells, but the frequency with which individual kinases are activated in primary tumors remains largely unknown. We used a computational approach, termed kinase-substrate enrichment analysis (KSEA), to systematically infer the activation of given kinase pathways from mass spectrometry-based phosphoproteomic analysis of acute myeloid leukemia (AML) cells. Experiments conducted in cell lines validated the approach and, furthermore, revealed that DNA-dependent protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
388
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 336 publications
(393 citation statements)
references
References 61 publications
5
388
0
Order By: Relevance
“…S2. Motif analysis (14) further revealed that the inhibitor pairs exhibited strongly correlated impacts on specific phosphorylation motifs while mirroring the relationships seen in Fig. 1 C and D (Fig.…”
Section: Phosphoproteomics Data Allow the Classification Of Kinase Inmentioning
confidence: 84%
See 4 more Smart Citations
“…S2. Motif analysis (14) further revealed that the inhibitor pairs exhibited strongly correlated impacts on specific phosphorylation motifs while mirroring the relationships seen in Fig. 1 C and D (Fig.…”
Section: Phosphoproteomics Data Allow the Classification Of Kinase Inmentioning
confidence: 84%
“…Phosphorylated peptides were enriched through the use of TiO 2 beads (GL Sciences) in a similar manner to that previously described (14,19) with some modifications, and analyzed by LC-MS/MS using a LTQ-Orbitrap mass spectrometer. Peptides were identified by means of Mascot searches against the SwissProt human protein database.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations